Analyzing Motivation in Junior High School Students’ Reading Habits - Kalila, Dwi Duvanny; Prasetyaningrum, Ari; Suherman, Andri; Maysuroh, Siti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines junior high school students’ motivation in developing reading habits and identifies the supporting and hindering factors. A mixed-method design was applied, involving questionnaires completed by 64 students at SMPN 2 Sikur, as well as interviews and classroom observations. Findings revealed that most students demonstrated moderate (39.06%) to high (32.81%) levels of reading motivation, with an overall average of 3.15. Intrinsic factors, such as curiosity, enjoyment, and the desire for knowledge, emerged as the strongest drivers, while extrinsic factors, including encouragement from teachers and parents, played a role but inconsistently. Major obstacles included boredom, limited time, and difficulties in understanding texts, particularly in foreign languages. The school environment, such as poorly maintained libraries and the lack of literacy activities, was also found to be unsupportive. These results indicate that intrinsic motivation is crucial for fostering reading habits, yet it must be reinforced by external support and a conducive learning atmosphere. The study suggests revitalizing school literacy programs